Assessment of self reported oral health attitudes and behaviors of a group of dental students using the Hiroshima University - dental behavioural inventory in Turkey - ŞEN YAVUZ, BETÜL; BEKİROĞLU, GÜLNAZ NURAL; KARGÜL, BETÜL (My University, 2023)
Purpose: Dental students play a crucial role in promoting positive oral health attitudes and behaviors among their relatives and patients. Students\" self reported oral health behaviors may tend to improve as they progress in their dental education. Therefore, this study aimed to assess the difference in self reported oral health behavior and attitudes of a group of Turkish first and final-year students using the Hiroshima University Dental Behavioural Inventory.Materials & Methods: In this cross-sectional study, 237 students, including first and final-year, studying at XXX University Faculty of Dentistry, were invited. Of these, 187 students (108 first, 73 final-year) agreed to participate. Eleven students (7 first-year, 4 final-year) who did not fill out the questionnaire were excluded. The Hiroshima University Dental Behavioural Inventory was used to measure the behaviors and attitudes of the students regarding oral and dental health. Additionally, three items other than HU-DBI were added to the questionnaire. The analysis was conducted using the Chi-square test, and Independent t-test.Results: The responses of 178 students (107 first-year, 69 final-year; 122 female, 54 male) were analyzed. The self reported oral health behavior scores of the final-year students (6.21 ± 1.54) were statistically higher than the scores of the first-year students (5.03 ± 1.76) (p < 0.001). Although the score was slightly higher in females (5.57 ± 1.96) compared to males (5.33 ± 1.27), the difference was not statistically significant (p = 0.334).Conclusions: According to the results of this study, education may have a significant positive effect on self reported oral health behavior and attitude of dental students. Based on the findings of university-based evaluations as this study, curricula that can gain positive attitudes to students and oral hygiene programs aimed at improving students\" self-care should be developed from the early years. However, further studies that also evaluate the effect of possible confounding variables on oral health behavior should be done to clearly highlight the impact of education.Keywordsdental student,education level,health-behavior
Keywords: Tıp; Diş Hekimliği; Klinik Bilimler; Diğer; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Dentistry; Clinical Sciences; Other; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; DENTISTRY, ORAL SURGERY & MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; dental student; education level; health-behavior